Pengaruh Servant Leadership terhadap Organizational Citizenship Behavior (OCB) melalui Komitmen Organisasi pada Sekretariat Daerah Kabupaten Tanjung Jabung Barat - Lucy Rachelda Septian; Shofia Amin; Besse Wediawati (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
The aim of this research is to have an overview of servant leadership, organizational commitment and Organizational Citizenship Behavior (OCB) at the Regional Secretariat of West Tanjung Jabung Regency and to analyze the influence of servant leadership on Organizational Citizenship Behavior (OCB) mediated by organizational commitment at the Regional Secretariat of West Tanjung Jabung Regency. The analysis tool used is PLS. The research results show that the leadership in this agency shows good leadership attitudes. Organizational commitment at the Regional Secretariat of West Tanjung Jabung Regency, it can be seen that the level of employee commitment to the organization as a whole is relatively high. Meanwhile, Organizational Citizenship Behavior (OCB) at the Regional Secretariat of West Tanjung Jabung Regency, overall it can be concluded that the OCB of employees in this agency is in the Fairly High category. Servant leadership has a positive and significant effect on organizational commitment. Servant leadership has a positive and significant effect on Organizational Citizenship Behavior. Organizational commitment has a positive and significant effect on Organizational Citizenship Behavior. Servant leadership has a positive and significant effect on Organizational Citizenship Behavior through the organizational commitment of employees at the Regional Secretariat of West Tanjung Jabung Regency.